Policing Protest in the Austerity-driven Slovenia - Rak, Joanna (Wydawnictwo Naukowe WNPiD UAM, 2019)
This article aims to evaluate protest policing in the austerity-driven Slovenia and verify the analytical effectiveness of a tool for measuring protest policing. Therefore, the paper critically discusses and modifies Donatella della Porta and Herbert Reiter’s theoretical framework consisting of the escalated force and negotiated management antinomic ideal types, and then applies it to examine the Slovenian case. The research draws on a qualitative method of sources analysis based on a conceptual qualitative content analysis to solve the problems of what was the Slovenian model of protest policing in times of austerity? And why did it have a particular shape? The study diagnoses Slovenia as having the negotiated management mode of protest policing with the elements of the escalated force model. This mode stems from the organizational dynamics of the Slovenian National Police which typifies with the dialectic of decentralization and hierarchical submission in police units, the effectively used possibilities to coordinate the different groups operating within protesting crowds, and certainty about the purposes of the intervention.

Celem artykułu jest ocena polityki kontroli protestu w Słowenii w okresie wychodzenia z kryzysu ekonomicznego oraz weryfikacja analitycznej efektywności narzędzia do pomiaru kontroli protestu. Tekst prezentuje krytyczną dyskusję nad modelem teoretycznym składającym się z antynomicznych typów idealnych eskalowanej siły i negocjowanego kierowania autorstwa Donatelli della Porty i Herberta Reitera. Następnie, wykorzystuje je w roli narzędzia do zanalizowania słoweńskiego przypadku. W badaniu zastosowano jakościową metodę analizy źródeł opartą na konceptualnej jakościowej analizie zawartości, żeby rozwiązać następujące problemy badawcze: jaki model kontroli protestu wystąpił w Słowenii w okresie implementacji polityki surowości? I dlaczego kontrola przybrała taką formę? Studium pokazuje, że w Słowenii pojawił się model negocjowanego kierowania z elementami eskalowanej siły. Ten typ kontroli protestu wynikał z organizacyjnej dynamiki Słoweńskiej Policji Narodowej, która odznacza się dialektyką decentralizacji i hierarchicznego podporządkowania w oddziałach policji, efektywnym wykorzystywaniem możliwości koordynacji różnych grup działających w obrębie protestujących tłumów oraz pewnością co do celów interwencji.
Polityka kontroli protestu w Słowenii w okresie wychodzenia z kryzysu ekonomicznego
Keywords: protest policing; culture of political violence; Slovenian National Police; protest movement; political demonstration; polityka kontroli protestu; kultura przemocy politycznej; Słoweńska Policja Narodowa; ruch protestu; demonstracja polityczna